Paradoxical Strategies for Winning Change in Government Bureaucracy - Kamaruddin, Kamaruddin; Ikhsan, Masrul (Universitas Padjadjaran, 2025)
Bureaucratic reform in Indonesia has been a primary focus in efforts to enhance government efficiency and transparency. However, despite the implementation of various reform policies, data reveals that many government agencies still face challenges in implementing significant changes. This research aims to analyze the factors hindering the success of reforms, effective strategies to drive change, and the role of technology and political support in the process. The study focuses on the National Institute of Public Administration (LAN) as a case study due to its crucial role in Indonesia's bureaucratic reform. The findings indicate that paradoxical approaches, such as creating flexible roadmaps and promoting informal communication, can strengthen reform effectiveness. Additionally, consistent political support and ongoing training for employees are identified as key factors in fostering innovation and change within the bureaucracy. This study offers practical recommendations for decision-makers to improve the success of bureaucratic reform in Indonesia.